2012
DOI: 10.5415/apallergy.2012.2.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Lack of efficacy of a herbal preparation (RCM-102) for seasonal allergic rhinitis: a double blind, randomised, placebo-controlled trial

Abstract: BackgroundA herbal preparation, known as RMIT Chinese Medicine 102 (RCM-102) consisting of eight herbs which demonstrates inhibition of the release of key inflammatory mediators associated with seasonal allergic rhinitis (SAR) was used. This study evaluated the efficacy and safety of RCM-102 for SAR.ObjectiveThis study evaluated the efficacy and safety of RCM-102 for SAR.MethodsThis randomised placebo-controlled trial involved subjects aged between 18 and 65 who were randomly assigned to either RCM-102 or a pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Finally, 12 trails documented in 11 articles were enrolled in the meta-analysis. 8 9 12 19 21 22 23 24 25 26 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 12 trails documented in 11 articles were enrolled in the meta-analysis. 8 9 12 19 21 22 23 24 25 26 27 …”
Section: Resultsmentioning
confidence: 99%
“…Although occurrence of adverse events was one of the outcomes to be assessed in the present meta-analysis, it was not possible to perform this analysis because the occurrence of adverse events following CHM treatment was reported as an outcome measure in only one of the enrolled studies. 25 This clearly suggests that further studies on CHM treatment-associated adverse events are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Hsu and colleagues 396 investigated the effect of herbal point-patch treatment in AR patients and showed that acupoint herbal point-patches were an effective treatment for improvement in quality of life in AR. Besides studies in Chinese patients, some randomized trial also assessed the efficacy of CHM in Korean, 397 Australian 398 399 402 and German 400 patients with AR. Although 2 meta-analysis of clinical trials on traditional CHM for the treatment of AR revealed that CHM interventions appeared to have beneficial effects in patients with AR, 321 402 some clinical trials subsequently provided conflicting data for the potential efficacy of CHM for AR 399 402 Particularly when the effect of CHM was assessed in combination with acupuncture for the treatment of SAR.…”
Section: Treatmentmentioning
confidence: 99%
“…Besides studies in Chinese patients, some randomized trial also assessed the efficacy of CHM in Korean, 397 Australian 398 399 402 and German 400 patients with AR. Although 2 meta-analysis of clinical trials on traditional CHM for the treatment of AR revealed that CHM interventions appeared to have beneficial effects in patients with AR, 321 402 some clinical trials subsequently provided conflicting data for the potential efficacy of CHM for AR 399 402 Particularly when the effect of CHM was assessed in combination with acupuncture for the treatment of SAR. While one study from Germany 400 demonstrated that CHM combined with acupuncture significantly improved both symptoms and quality of life scores in SAR patients compared to acupuncture treatment alone, another study from Australia 402 failed to show any significant differences in symptomatic relief or improvement in quality-of-life scores in SAR patients treated with CHM + acupuncture or acupuncture alone.…”
Section: Treatmentmentioning
confidence: 99%
“…Readers may have a new idea how to set up a clinical trial of herbal preparation like RCM-102 although it was found to be not an effective preparation for seasonal allergic rhinitis [8]. …”
mentioning
confidence: 99%